Chemo- and optogenetic activation of hypothalamic Foxb1-expressing neurons and their terminal endings in the rostral-dorsolateral PAG leads to tachypnea, bradycardia, and immobility - Cola, Reto; Roccaro-Waldmeyer, Diana M.; Naim, Samara; Babalian, Alexandre; Seebeck, Petra; Alvarez-Bolado, Gonzalo; Celio, Marco R. (eLife, 2024)
Foxb1 -expressing neurons occur in the dorsal premammillary nucleus (PMd) and further rostrally in the parvafox nucleus, a longitudinal cluster of neurons in the lateral hypothalamus of rodents. The descending projection of these Foxb1+ neurons end in the dorsolateral part of the periaqueductal gray (dlPAG). The functional role of the Foxb1+ neuronal subpopulation in the PMd and the parvafox nucleus remains elusive. In this study, the activity of the Foxb1+ neurons and of their terminal endings in the dlPAG in mice was selectively altered by employing chemo- and optogenetic tools. Our results show that in whole-body barometric plethysmography, hM3Dq-mediated, global Foxb1+ neuron excitation activates respiration. Time-resolved optogenetic gain-of-function manipulation of the terminal endings of Foxb1+ neurons in the rostral third of the dlPAG leads to abrupt immobility and bradycardia. Chemogenetic activation of Foxb1+ cell bodies and ChR2-mediated excitation of their axonal endings in the dlPAG led to a phenotypical presentation congruent with a 'freezing-like' situation during innate defensive behavior.